2020
DOI: 10.33963/kp.15640
|View full text |Cite
|
Sign up to set email alerts
|

New hope for patients and challenges for the multidisciplinary arrhythmia team: a hybrid convergent approach for atrial fibrillation treatment

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives 4.0 International License (CC BY-NC-ND 4.0), allowing third parties to download articles and share them with others, provided the original work is properly cited, not changed in any way, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It can also be confirmed by the analysis of patients with CHF included in the CABANA trial, in which additional ablation lines, parasympathetic ganglion ablation, or an ablation strategy based on the recording of local atrial potentials were allowed [19]. The high efficacy of hybrid ablation with minimally invasive access in the maintenance of the sinus rhythm could also support this approach [30,31].…”
Section: Discussionmentioning
confidence: 84%
“…It can also be confirmed by the analysis of patients with CHF included in the CABANA trial, in which additional ablation lines, parasympathetic ganglion ablation, or an ablation strategy based on the recording of local atrial potentials were allowed [19]. The high efficacy of hybrid ablation with minimally invasive access in the maintenance of the sinus rhythm could also support this approach [30,31].…”
Section: Discussionmentioning
confidence: 84%
“…Among recent single-arm studies, cardioversion for endocardial ablation ranged between 8.3% and 12.9%. [29][30][31] Buchta et al 32 also evaluated long-term cardioversion before and after hybrid ablation in AF and found a significant reduction in cardioversions 12 months after the procedure compared to 12 months before the procedure (p = .003). This was also true when the timeframe was extended to 3 years following the procedure compared to 3 years before the procedure (p = .015).…”
Section: Converge Trial Resultsmentioning
confidence: 99%
“…This was also true when the timeframe was extended to 3 years following the procedure compared to 3 years before the procedure (p = .015). 32 T A B L E 1 Cardioversion rates associated with the hybrid convergent procedure in published literature. The CONVERGE trial reported a 30-day MAE rate of 7.8%, which was below the protocol-specified safety goal.…”
Section: Converge Trial Resultsmentioning
confidence: 99%
“…However, more recent studies have not only shown a much lower risk of major complications (<2%), but also a significantly lower need for repeat procedures (<20%) [25,47,48]. Also, a small subset of patients with persistent and long-standing AF may benefit from a hybrid approach, integrating the strengths of both surgical and catheter ablation [69,70]. There are also limited data regarding AF ablation and left atrial appendage occlusion performed as a single procedure; to integrate the 'cure' for AF and prevent stroke complications, in order to avoid the risk associated with repeated procedures [71][72][73].…”
Section: Expert Opinion On the Future Of Af Managementmentioning
confidence: 99%